(untitled) (Physical Education, Health and Social Sciences, 2026)
Background: Stroke is a serious medical condition that can be very challenging to deal with and the aftereffects of stroke are very serious, the patient’s disability to do daily life work and dependence on others can be detrimental to his mental health. Many factors are associated with the quality of life of stroke patients like the ability to perform ADLs, mental well-being, etc. Objectives: The study aims to compare factors related to quality of life among ischemic and hemorrhagic stroke. Methods: A cross-sectional comparative study was carried out among 100 stroke survivors (mean age 80) in different Hospitals in Punjab with the help of convenient sampling. The tools of measurement were WHOQOL-BREF, SAQOL-39 scale, Barthel Index, Modified Rankin Scale, and Mississippi Aphasia Screening test (MAST). Descriptive and inferential statistics using SPSS version 26 were done to explore correlations between stroke type and factors of QoL. Results: The comparison between ischemic and hemorrhagic stroke groups across various measures showed mixed results in terms of statistical significance. The Barthel Index demonstrated a substantial difference (p < 0.001), indicating better functional outcomes in the ischemic group (mean difference 9.40000). Other measures, including SAQOL39 (p = 0.836), MAST (p = 0.339), and all domains of WHOQOL (Physical: p = 0.802, Psychological: p = 0.192, Social: p = 0.075, Environment: p = 0.993), did not reveal statistically significant differences between the groups. Conclusions: These findings suggest that while functional independence significantly favors ischemic stroke patients, quality of life and psychological well-being showed no clear differences between ischemic and hemorrhagic stroke types based on the analyzed metrics.